The INVENT COVID trial: a structured protocol for a randomized controlled trial investigating the efficacy and safety of intravenous imatinib mesylate (Impentri®) in subjects with acute respiratory distress syndrome induced by COVID-19 - Atmowihardjo, Leila; Schippers, Job R.; Bartelink, Imke H.; Bet, Pierre M.; van Rein, Nienke; Purdy, Keith; Cavalla, David; Comberiati, Valérie; McElroy, Andrew; Snape, Sue D.; Bogaard, Harm Jan; Heunks, Leo; et al. (Current controlled trials in cardiovascular medicine, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has led to a disruptive increase in the number of intensive care unit (ICU) admissions with acute respiratory distress syndrome (ARDS). ARDS is a severe, life-threatening medical condition characterized by widespread inflammation and vascular leak in the lungs. Although there is no proven therapy to reduce pulmonary vascular leak in ARDS, recent studies demonstrated that the tyrosine kinase inhibitor imatinib reinforces the endothelial barrier and prevents vascular leak in inflammatory conditions, while leaving the immune response intact. This is a randomized, double-blind, parallel-group, placebo-controlled, multicenter clinical trial of intravenous (IV) imatinib mesylate in 90 mechanically ventilated subjects with COVID-19-induced ARDS. Subjects are 18 years or older, admitted to the ICU for mechanical ventilation, meeting the Berlin criteria for moderate-severe ARDS with a positive polymerase chain reaction test for SARS-CoV2. Participants will be randomized in a 1:1 ratio to either imatinib (as mesylate) 200 mg bis in die (b.i.d.) or placebo IV infusion for 7 days, or until ICU discharge or death. The primary study outcome is the change in Extravascular Lung Water Index (EVLWi) between day 1 and day 4. Secondary outcome parameters include changes in oxygenation and ventilation parameters, duration of invasive mechanical ventilation, number of ventilator-free days during the 28-day study period, length of ICU stay, and mortality during 28 days after randomization. Additional secondary parameters include safety, tolerability, and pharmacokinetics. The current study aims to investigate the efficacy and safety of IV imatinib in mechanically ventilated subjects with COVID-19-related ARDS. We hypothesize that imatinib decreases pulmonary edema, as measured by extravascular lung water using a PiCCO catheter. The reduction in pulmonary edema may reverse hypoxemic respiratory failure and hasten recovery. As pulmonary edema is an important contributor to ARDS, we further hypothesize that imatinib reduces disease severity, reflected by a reduction in 28-day mortality, duration of mechanical ventilation, and ICU length of stay. Protocol version and date: V3.1, 16 April 2021. Recruitment started on 09 March 2021. Estimated recruitment period of approximately 40 weeks. ClinicalTrials.gov NCT04794088 . Registered on 11 March 2021.